Оценка влияния коллизий на производительность сети Ethernet - Гулиус, В. А.; Янковский, А. А. (ХНУРЭ, 2008)
For a rate of influencing of collisions on output of Ethernet the program was designed in environment MatLab. This program was used for simulation which has permitted to receive the evaluation performances of collisions influencing on throughput capacity of a network was executed. In result the profiles which have permitted to execute a visual rate of degradation of a network were built aroused collisions
Keywords: производительность сети Ethernet